Low molecular weight hyaluronan mediated CD44 dependent induction of IL-6 and chemokines in human dermal fibroblasts potentiates innate immune response - Vistejnova, Lucie; Safrankova, Barbora; Nesporova, Kristina; Slavkovsky, Rastislav; Hermannova, Martina; Hosek, Petr; Velebny, Vladimir; Kubala, Lukas (Cytokine, 2014)
Complex regulation of the wound healing process involves multiple interactions among stromal tissue cells, inflammatory cells, and the extracellular matrix. Low molecular weight hyaluronan (LMW HA) derived from the degradation of high molecular weight hyaluronan (HMW HA) is suggested to activate cells involved in wound healing through interaction with HA receptors. In particular, receptor CD44 is suggested to mediate cell response to HA of different MW, being the main cell surface HA receptor in stromal tissue and immune cells. However, the response of dermal fibroblasts, the key players in granulation tissue formation within the wound healing process, to LMW HA and their importance for the activation of immune cells is unclear. In this study we show that LMW HA (4.3kDa) induced pro-inflammatory cytokine IL-6 and chemokines IL-8, CXCL1, CXCL2, CXCL6 and CCL8 gene expression in normal human dermal fibroblasts (NHDF) that was further confirmed by increased levels of IL-6 and IL-8 in cell culture supernatants. Conversely, NHDF treated by HMW HA revealed a tendency to decrease the gene expression of these cytokine and chemokines when compared to untreated control. The blockage of CD44 expression by siRNA resulted in the attenuation of IL-6 and chemokines expression in LMW HA treated NHDF suggesting the involvement of CD44 in LMW HA mediated NHDF activation. The importance of pro-inflammatory mediators produced by LMW HA triggered NHDF was evaluated by significant activation of blood leukocytes exhibited as increased production of IL-6 and TNF-α. Conclusively, we demonstrated a pro-inflammatory response of dermal fibroblasts to LMW HA that was transferred to leukocytes indicating the significance of LMW HA in the inflammatory process development during the wound healing process.
Keywords: Fibroblasts; chemokiny; signální transdukce; Immunity, Innate; Signal Transduction; Hyaluronan Receptors; Humans; messenger RNA; Leukocytes; IL-8; molekulová hmotnost; Interleukin-6; Interleukin-8; Inflammation; interleukin-8; Dermis; lidé; IL-6; antigeny CD44; Hyaluronan; TNF-alfa; RNA, Small Interfering; RNA, Messenger; malá interferující RNA; interleukin-6; kyselina hyaluronová; škára; Tumor Necrosis Factor-alpha; fibroblasty; Inflammation Mediators; leukocyty; Hyaluronic Acid; mediátory zánětu; přirozená imunita; Chemokines; Molecular Weight